PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS CONTEXTUAL TEACHING LEARNING (CTL) MATERI HIMPUNAN KELAS VII SMP - SHOLEHAH, SITI (Universitas Pasir Pengaraian, 2016)
AbstractThe research proposes to make Student Worksheet base on CTL valid and simply on Set. Research type uses research and development (R & D). There were three research steps, those defining, design, and development. Research subject was 7th grade secondary school students SMP Negeri 2 Pagaran Tapah Darussalam 2015/2016 school year. Instruments used on research were validation sheets and questionnaire. Process to get Student Worksheet that valid and practice involve defining, design, and development. On development step Student Worksheet validated four validator by get average validation 3,20 with valid category. While practicalities got by experiment and research by practicalities questionnaire expert who get practicalities value 80,00% in practical category. Practical experiment by teacher whose get practicalities 78,41%. In practical category, and practical experiment by 7th grade SMP Negeri 2 Pagaran Tapah Darussalam who get practical value 86,68% in very practical category. Finally conclude Student Worksheet base on CTL valid and practical.